Observed Pattern Of Radiculopathy In The Upper Limb - Siddharth; R Deepak; Bhawna (Revista Electronica de Veterinaria, 2024)
Background: Upper limb radiculopathy, commonly caused by cervical nerve root compression, is characterized by pain, sensory deficits, and motor weakness. Understanding the patterns of clinical presentations and imaging findings is critical for accurate diagnosis and targeted treatment.Objective: This study aimed to investigate the observed patterns of radiculopathy in the upper limb, focusing on demographic trends, clinical features, and radiological findings to provide a comprehensive understanding of the condition.Methods: A cross-sectional observational study was conducted on 50 patients aged 18–65 years with clinically diagnosed upper limb radiculopathy. Detailed history, physical examination, and magnetic resonance imaging (MRI) were performed to evaluate nerve root involvement and underlying pathologies. Data were analyzed to identify trends in symptom distribution, nerve root involvement, and imaging findings. Results: The majority of patients were aged 30–50 years, with a slight male predominance. The C6 and C7 nerve roots were most commonly affected. Pain was the predominant symptom, often accompanied by numbness or motor weakness. MRI findings revealed disc herniation as the leading cause, followed by foraminal stenosis and spondylosis. Strong correlations were observed between clinical findings and radiological results. Conclusion: This study highlights the prevalence of C6 and C7 radiculopathy, with pain as the most frequent presenting symptom. Disc herniation remains the primary etiological factor. The findings underscore the importance of combining clinical assessment with advanced imaging for effective diagnosis and management. Further research with larger sample sizes is recommended to explore long-term outcomes and treatment efficacy.